BORDER SAFETY : KAMPUNG MONGKOS TEBEDU SERIAN SARAWAK - Zaimuariffudin Shukri, Nordin; Eva Kristin, Larry Sait; Abang Izhar, Abang Ahmad; Mohamad Hardyman, Barawi (Persatuan Promosi Matlamat Pembangunan Lestari, 2023)
This case study was conducted in Kampung Mongkos, a village located within the Serian parliamentary constituency and close to the border between Malaysia and Indonesia. The proximity of this village to this international border renders it an area prone to activities contrary to both international and domestic laws. During the site visit and interview session, the researcher acquired information on security vulnerabilities, which the Malaysian government needs to address. Among these vulnerabilities is the issue of smuggling involving both humans and merchandises. Despite the fact that Kampong Mongkos is the closest village to the border, the security post of the Customs, Immigration, and Quarantine (CIQ) of Malaysia is located not in this village, but in a village approximately seven kilometres from the border. Therefore, this study emphasises on the importance of raising the level of security along the Malaysia-Indonesia border, particularly with regards to Kampong Mongkos.